A inserção no mercado de trabalho dos participantes do Exame Nacional de Revalidação de Diplomas Médicos - REVALIDA - Santos, Saulo Teixeira dos (2022)
The objective of the research is to understand how the insertion in the Brazilian labor market of the participants of the National Examination for Revalidation of Medical Diplomas Issued by Foreign Education Institutions – Revalida behaves. The research analyzes data related to the exam, together with the database from the Annual Report of Social Information - RAIS. The first step is to identify the individuals who participated in the Exam in 2015, who passed all stages and proceed with the crossing of the information of these individuals with the RAIS 2018 database. Thus, we seek to understand the characteristics of these individuals and verify if these doctors, after passing the Exam, are effectively managing to work in the medical job market in Brazil. We could observe that, for the analyzed cohort, 42% of the total approved work in the Brazilian formal market. As secondary results, there was a gender equality of those approved, a predominance of work relationships in public entities and a greater number of undergraduates from South America, both in terms of the nationality of doctors and diplomas.